Diversity and Structure of Insect Communities in Rice Paddy Ecosystems in Tanah Miring District Merauke Regency - Gora Guratmana; Jefri Sembiring; Johana Anike Mendes; Anwar Anwar; Mani Yusuf; Rizki Al Khairi Barus (JURNAL AGRIMENT, 2026)
The objective of this study was to analyze insect diversity and community structure in rice plants across three ecosystem types: rice fields bordering forests, swamps, and settlements. The study was conducted from April to July 2025 in Tanah Miring District, Merauke Regency, South Papua Province. At each location, five observation plots measuring 5 × 5 m² were established. Sampling was carried out using the sweep net method during the vegetative and generative growth stages of rice. Data were analyzed using the Shannon–Wiener diversity index (H’), evenness index (E), and dominance index (C). The results showed that insect communities were dominated by pest groups across all ecosystem types. Rice fields bordering forests exhibited the highest insect abundance and natural enemy populations, while swamp-adjacent ecosystems showed lower abundance but more even distribution of individuals, indicating relatively stable community conditions. In contrast, ecosystems bordering settlements were strongly dominated by pests, particularly the family Cicadellidae, reflecting ecological imbalance due to environmental pressure, agricultural intensification, and pesticide use. The diversity index was moderate (H’ = 1.98–2.41), evenness was high (E = 0.73–0.91), and dominance was low to moderate (C = 0.14–0.24), indicating relatively stable community conditions.Varietal differences revealed that Cigelis and Agritan tended to have higher pest populations, whereas Inpari 32 and Inpari 42 exhibited a more balanced community structure. Landscape factors play a crucial role in shaping insect communities; therefore, ecologically based integrated pest management is essential to maintain the sustainability of rice agroecosystems.